The proposed amendments to laws on malay reservation land: a study on its economic impact on malay reservation landowners in Kampung Kuantan, Klang / Nur Fadhilah Mat Yusoff..[et al.] - Mat Yusoff, Nur Fadhilah; Habib, Sri Wahyuni; Ismail, Nurliana; Blayau, Jessie (2005)
Malay reservation land refers to that specific category of lands situated within the territorial boundaries of each state in Peninsular Malaysia which can only be owned or held by Malays, as constituted in Article 89(6) of the Federal Constitution. Dealings in respect of such land such as transfers, leases, charges and easements, can only be transacted amongst the Malays, and any attempt by non-Malays in dealing with such Malay reservation land will be held null and void. Recently, there is a proposal made to amend the Malay Reserve Enactment in order to allow leasing of Malay reservation lands to non-Malays for development as an alternative way to solve some of the long standing problems undermining the economics of Malay reservation lands. The objective of this research is to examine and evaluate the proposed amendment on its economic impact to Malay reservation landowners in Kampung Kuantan, Klang. The methodologies that adopted in obtaining the data are through library research for books, law journals, seminar papers and other sources related to this topic. Interviews also are carried out with the relevant people involved in this field. Some data also is taken from the Internet. Recommendations be made to change the misconceptions of the Malay reservation landowners that the proposed amendments of Malay Reservation Enactment will not threaten their rights and title over Malay reservation lands, but it confers full economic potential in developing their land.